Revenues, Expenses and Savings - Variables of Influence - Mălina-Ionela Burlacu; Alexandru Bîrsan (Ovidius University Annals: Economic Sciences Series, 2020)
At the level of any society, income and expenditure and savings have played and continue to play an important role both from a macroeconomic perspective and from a microeconomic perspective. The purpose of our paper is to identify the variables of influences between the revenues, the expenses and the savings at a household level, by using the Principal Component Analysis. We have used the results of a questionnaire conducted on a sample of 344 persons nationally representative and we have used SPSS and Monte Carlo PCA in order to analyze the results and Identify the principal components.